2012
DOI: 10.1523/jneurosci.6350-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Jedi-1 and MEGF10 Signal Engulfment of Apoptotic Neurons through the Tyrosine Kinase Syk

Abstract: During the development of the peripheral nervous system there is extensive apoptosis and these neuronal corpses need to be cleared to prevent an inflammatory response. Recently, Jedi-1 and MEGF10, both expressed in glial precursor cells, were identified in mouse as having an essential role in this phagocytosis (Wu et al., 2009); however, the mechanisms by which they promote engulfment remained unknown. Both Jedi-1 and MEGF10 are homologous to the Drosophila melanogaster receptor Draper, which mediates engulfme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 53 publications
2
71
0
Order By: Relevance
“…Work on Drosophila Draper represents a good example of how basic cellular mechanisms can be elucidated in Drosophila glia and will teach us about mammalian glial cell biology. Recent work has shown that DRG satellite cells also use MEGF10/Jedi signaling (the mammalian orthologs of Draper/CED-1) to engulf cell corpses during mammalian nervous system development (Wu et al 2009), and that MEGF10 also activates an Src family signaling cascade similar to Src42a and Shark (Scheib et al 2012). Moreover, Chung et al (2013) recently discovered an exciting and conserved role for MEGF10 in astrocyte engulfment of synapses during neural circuit refinement in the mammalian visual system (Chung et al 2013).…”
Section: Gtpmentioning
confidence: 99%
“…Work on Drosophila Draper represents a good example of how basic cellular mechanisms can be elucidated in Drosophila glia and will teach us about mammalian glial cell biology. Recent work has shown that DRG satellite cells also use MEGF10/Jedi signaling (the mammalian orthologs of Draper/CED-1) to engulf cell corpses during mammalian nervous system development (Wu et al 2009), and that MEGF10 also activates an Src family signaling cascade similar to Src42a and Shark (Scheib et al 2012). Moreover, Chung et al (2013) recently discovered an exciting and conserved role for MEGF10 in astrocyte engulfment of synapses during neural circuit refinement in the mammalian visual system (Chung et al 2013).…”
Section: Gtpmentioning
confidence: 99%
“…Src family kinases (SFKs) are cytosolic nonreceptor tyrosine kinases that promote microglia activation triggered by different inflammatory stimuli (45)(46)(47)(48)(49)(50). Classical microglial stimulation with LPS increases the activity of SFKs, including the prototypical and founding member c-Src (36,51).…”
Section: C-src Activation In Microglia Decreases Svct2 On the Plasmamentioning
confidence: 99%
“…Specifically, we looked for the presence of pyknotic nuclei, highly condensed chromatin suggestive of dead cells (Savill et al, 2002). We dissected brains from 1-d-old …”
Section: Apoptotic Corpses Persist In Drprmentioning
confidence: 99%
“…Drosophila melanogaster has been a powerful model for understanding glia-dependent phagocytosis and neurodegenerative diseases (Shulman et al, 2003;Fullard et al, 2009). The CED-1 ortholog Draper (Drpr) is an important recognition receptor for glia-dependent phagocytosis .…”
Section: Introductionmentioning
confidence: 99%